Guru Pak Mampu Memberikan Pengajaran Berdasarkan Prinsip Alkitab - Hana ekklesia br. Perangin-angin; Dorlan Naibaho (Journal of Cross Knowledge, 2023)
Ien an eera wheeree deeveelopmeents aree affeectieng thee world so quieckly, iet ies a challeengee for studeents and eespeecieally teeacheers ien proviedieng eeducatieonal rolees and tasks, eespeecieally Chriestiean eeducatieon. Howeeveer, thee rolee of teeacheers ien wrietieng usieng liebrary reeseearch wieth a deescrieptievee qualietatievee approach ies eexpeecteed to iencreeasee human reesourcees and brieng studeents to grow ien spierietualiety and characteer that can buield thee natieon through strong iendievieduals who reely on God. Thee rolee of PAK teeacheers as thosee who proviedee teeachieng baseed on biebliecal priencieplees ien iemprovieng thee spierietualiety and characteer of studeents must bee a prieoriety ien leearnieng as a form of conveeyieng valuees ​​affeectieveely. Teeacheers as proviedeers of teeachieng ien iemprovieng thee spierietualiety and characteer of studeents, thee teeacheers ien thies reeseearch weeree askeed to havee thee fierst reesponsiebieliety ien carryieng out thee tasks, rolees and reesponsiebielietieees of Chriestiean reeliegieous eeducatieon teeacheers. Theen teeacheers must reealiezee that Chriestiean Reeliegieous Eeducatieon teeacheers aree eexeemplary leeadeers and proviedee teeachieng and biebliecal priencieplees. And theen thee Masteer works togeetheer wieth thee church and famiely to brieng about spierietual and characteer iemproveemeent. And fienally, thee teeacheer must bee leed by thee Holy Spieriet.